Dialogic Signals In Argumentative Discussions of Advanced Polish Learners Of English - Nowicka, Agnieszka (Wydawnictwo Naukowe UAM, 2001)
The first part of the paper deals with characteristics of classroom interaction as a type of institutional talk in a conversational analytic perspective. Next, the thesis is discussed concerning developing learners' interactional competence to foster learner discursive independence in argumentative discussions in English as a foreign language. Finally, after a short review of dialogic signals, the article presents a preliminary analysis of selected dialogic signals: evaluating reformulations and piggybacking as the ways of achieving reciprocity in argumentative discussions.
Keywords: dialogic signals; argumentative discussions; Polish learners of English